Ultraviolet and infrared excitable inorganic-organic hybrid materials: Synthesis, characterization and anti-counterfeiting applications. (February 2023) - Qiu, Haijiang; Li, Min; Lu, Yongfeng; Cheng, Hongrui; Chen, Haixin; Zheng, Yuanhui
Abstract: Luminescence materials have received extensive attention for anti-counterfeiting applications due to their low-cost fabrication and simple verification advantages. However, single-emitting encryption can be easily cracked. Therefore, the development of multi-responsive anti-counterfeiting strategies is urgent. Here, we report a facile and universal method to fabricate ultraviolet and infrared excitable inorganic-organic hybrid materials that consist of up-conversion nanoparticles (UCNPs) and organic afterglow materials. With this method, UCNPs can be assembled onto organic afterglow materials driven by the electrostatic interactions between the two components. As a proof-of-concept, a NaYF4 : Yb, Er UCNPs@catechol-doped cyanuric acid (cd-CA) composite was designed and served as a secret anti-counterfeiting ink material. The security label using the hybrid material as an information carrier shows multiple encryption signals, such as fluorescence, up-conversion, phosphorescence, and infrared thermal imaging, increasing security. Graphical abstract: Image 1 Highlights: This material of UCNPs@cd-CA possesses rich optical response ( e.g., fluorescence, upconversion fluorescence, phosphorescence, and infrared thermal imaging) and excellent moisture resistance. The strategy of utilizing electrostatic interactions to prepare hybrid materials with multiple optical properties has the advantages of being simple, robust and versatile. The physical mechanism of the quadruple optical response of its inorganic-organic hybrid material is revealed. A novel and unique dynamic anti-counterfeiting label based on UCNPs@cd-CA, with both visible and covert coding.